2017
DOI: 10.1128/msphere.00146-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Bacterial Community Composition and Structure in Clinically Symptomatic and Asymptomatic Central Venous Catheters

Abstract: Totally implanted venous access ports (TIVAPs) are commonly used implants for the management of acute or chronic pathologies. Although their use improves the patient’s health care and quality of life, they are associated with a risk of infection and subsequent clinical complications, often leading to implant removal. While all TIVAPs appear to be colonized, only a fraction become infected, and the relationship between nonpathogenic organisms colonizing TIVAPs and the potential risk of infection is unknown. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…In our study, the isolated organisms likely represent a mix of attached, surface- or lumen-associated cells ( 33 , 34 ). We obtained diverse Gram-negative, Gram-positive, and fungal isolates, and S. epidermidis was the most predominant single species, which matches well with previous reports ( 36 , 45 , 47 ). However, if we had employed a culture-independent approach focused on sequencing, we anticipate that microorganisms would have been detected in nearly 100% of the catheters.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the isolated organisms likely represent a mix of attached, surface- or lumen-associated cells ( 33 , 34 ). We obtained diverse Gram-negative, Gram-positive, and fungal isolates, and S. epidermidis was the most predominant single species, which matches well with previous reports ( 36 , 45 , 47 ). However, if we had employed a culture-independent approach focused on sequencing, we anticipate that microorganisms would have been detected in nearly 100% of the catheters.…”
Section: Discussionsupporting
confidence: 90%
“…The Maki roll technique, which has low sensitivity for isolation of intraluminal bacteria ( 34 ), was combined with sonication to maximize the chances of detecting bacterial colonization. Recently, culture-independent approaches have shown that both “symptomatic” and “nonsymptomatic” catheters contain diverse microorganisms ( 45 47 ), with “symptomatic” catheters colonized at higher levels and the most numerically dominant organisms often being the only ones cultured. This could explain the commonly held dogma that some catheters are colonized and others are not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While planktonic cells are susceptible to environmental cues, mixed-species biofilm communities provide a stable environment, e.g ., they maintain viable phage and bacterial populations 9 or induce adaptive bacterial physiological responses 10 . Molecular interactions between pathogenic and non-pathogenic bacteria are also potentially important in understanding bacterial colonization patterns, as shown in the bacterial community parameters in central venous catheters 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a seductive hypothesis to explain the low risk of infection despite almost universal bacterial colonization is that the mature biofilm we observed may act as a protective microbiota on the surface of the ICPT [6,30,31]. Studying another type of indwelling device (totally implanted venous access port, TIVAP) using NGS, Stressmann et al [30] identified two distinct patterns of biofilm composition, depending on the status of the patient at TIVAP removal (clinical suspicion of infection ["symptomatic"] or not ["asymptomatic"]). Among samples from asymptomatic patients, they identified Herbaspirillum, Paracoccus and Stenotrophomonas maltophilia more abundantly than in symptomatic patients.…”
Section: Discussionmentioning
confidence: 89%